Răspuns :
[tex] \dfrac{1}{2}^{ \times 6} + \dfrac{1}{2}^{ \times 6} + \dfrac{1}{6}^{ \times 2} = \dfrac{6}{12} + \dfrac{6}{12} + \dfrac{2}{12} = \dfrac{14}{12} ^{ \div 2} = \dfrac{7}{6} [/tex]
[tex] \dfrac{2}{5} ^{ \times 2} + \dfrac{3}{2}^{ \times 5} + \dfrac{7}{10} = \dfrac{4}{10} + \dfrac{15}{10} + \dfrac{7}{10} = \dfrac{26}{10} ^{ \div 2} = \dfrac{13}{5} [/tex]
[tex] \dfrac{4}{9} ^{ \times 2} + \dfrac{1}{3} ^{ \times 6} + \dfrac{7}{18} = \dfrac{8}{18} + \dfrac{6}{18} + \dfrac{7}{18} = \dfrac{21}{18}^{ \div 3} = \dfrac{7}{6} [/tex]
[tex] \dfrac{1}{40} + \dfrac{3}{8}^{ \times 5} + \dfrac{7}{4}^{ \times 10} + \dfrac{1}{2}^{ \times 20} = \dfrac{1}{40} + \dfrac{15}{40} + \dfrac{70}{40} + \dfrac{20}{40} = \dfrac{106}{40}^{ \div 2} = \dfrac{53}{20} [/tex]